Conservative surgery in multiple cusp involvement in tricuspid valve endocarditis. Issue 3 (September 1991) - Anderson, J R; Scott, P; Nair, R U
Abstract : Tricuspid and mitral valve endocarditis caused by Staphylococcus epidermidis in a 57 year old previously healthy man with no history of drug abuse presented as bi-ventricular failure and multiple episodes of pulmonary emboli. He was treated for four weeks with intravenous antibiotics and had serial echocardiographic assessment of the vegetation on the tricuspid valve. This was followed by mitral valve replacement, local excision of vegetation from all the three cusps of the tricuspid valve, and autologous pericardial reconstruction of these cusps with functional assessment by perioperative transoesophageal echocardiography. Postoperative cardiac function was excellent and serial echocardiographic assessment confirmed satisfactory tricuspid valve function. This is believed to be the first recorded case in which autologous pericardial repair was used to reconstruct all the three cusps in a tricuspid valve after excision of vegetations.